Electro-optical interfacial effects on a graphene/π-conjugated organic semiconductor hybrid system - Araujo, Karolline A. S.; Cury, Luiz A.; Matos, Matheus J. S.; Fernandes, Thales F. D.; Cançado, Luiz G.; Neves, Bernardo R. A. (Beilstein Journal of Nanotechnology, 2018)
The influence of graphene and retinoic acid (RA) – a π-conjugated organic semiconductor – interface on their hybrid system is investigated. The physical properties of the interface are assessed via scanning probe microscopy, optical spectroscopy (photoluminescence and Raman) and ab initio calculations. The graphene/RA interaction induces the formation of a well-organized π-conjugated self-assembled monolayer (SAM) at the interface. Such structural organization leads to the high optical emission efficiency of the RA SAM, even at room temperature. Additionally, photo-assisted electrical force microscopy, photo-assisted scanning Kelvin probe microscopy and Raman spectroscopy indicate a RA-induced graphene doping and photo-charge generation. Finally, the optical excitation of the RA monolayer generates surface potential changes on the hybrid system. In summary, interface-induced organized structures atop 2D materials may have an important impact on both design and operation of π-conjugated nanomaterial-based hybrid systems.
Keywords: DFT calculations; graphene; organic semiconductors; scanning probe microscopy; self-assembly